Horned-OWL: Flying Further and Faster with Ontologies - Lord, Phillip; Gehrke, Björn; Larralde, Martin; Hastings, Janna; De Bortoli, Filippo; Overton, James A.; Balhoff, James P.; Warrender, Jennifer (Transactions on Graph Data and Knowledge)
Horned-OWL is a library implementing the OWL2 specification in the Rust language. As a library, it is aimed at processes and manipulation of ontologies, rather than supporting GUI development; this is reflected heavily in its design, which is for performance and pluggability; it builds on the Rust idiom, treating an ontology as a standard Rust collection, meaning it can take direct advantage of the data manipulation capabilities of the Rust standard library. The core library consists of a data model implementation as well as an IO framework supporting many common formats for OWL: RDF, XML and the OWL functional syntax; there is an extensive test library to ensure compliance to the specification. In addition to the core library, Horned-OWL now supports a growing ecosystem: the py-horned-owl library provides a Python front-end for Horned-OWL, ideal for scripting ontology manipulation; whelk-rs provides reasoning services; and horned-bin provides a number of command line tools. The library itself is now mature, supporting the entire OWL2 specification, in addition to SWRL rules, and the ecosystem is emerging into one of the most extensive for manipulation of OWL ontologies.